Identifikasi Sebaran Air Lindi (Leachate) Menggunakan Metode Geolistrik Self-Potential (SP) Di Tempat Pembuangan Akhir (TPA) Parit Enam Kota Pangkalpinang - Padilah, Hoirotul; Widyaningrum, Yekti; Kurniawan, Widodo Budi (Jurnal Riset Fisika Indonesia, 2021)
Garbage is a common pollutant that causes various negative impacts such as lack of aesthetic value to the environment, brings various types of diseases and clogs waterways. The waste is then transported and disposed of at the TPA. The Parit Six TPA in Pangkalpinang City accommodates around 150 tons of garbage every day. This will cause contamination of water, soil and ground water by leachate seeping from the pile of garbage exposed to rain. The leachate can be identified using the Geoelectric Self Potential (SP) method using a fixed base technique with a space between the electrodes of 5 m. Then obtained the results of data acquisition from 6 paths as many as 92 points. Furthermore, the resulting data will be corrected and processed to produce isopotential contours and topography. Based on isopotential contours and topography, the distribution of fluid in the area around the Parit Enam TPA Pangkalpinang City is spread in the northeast, southwest to the north of the study area. The fluid quality around the study site is known from the results of density and pH of the sample well water. These results show the distribution of leachate in the area around the Parit Enam TPA Pangkalpinang City is spread from the northeast to the southwest in the northern part of the research area and from the southwest to the southern part of the research area towards the northern part of the research area.